Diffusion of passive scalar in a finite-scale random flow - Schekochihin, A; Haynes, P; Cowley, S (2004)
A model of the decay of scalar variance in a single-scale random velocity field was considered. It was emphasized that in any laboratory experiment aiming to test the results, the stirring must be done at scales substantially smaller than the system size. The key factor was found to be the statistics of fluid displacements, which were integrals of velocity and were finite-time correlated even for a white-in-time velocity. A set up allows to show experimentally that the global mixing rate was much smaller than that predicted by the Lagrangian-stretching theories and consistent with the box-scale turbulent-diffusion rate.